Ð˜ÑÑÐ»ÐµÐ´Ð¾Ð²Ð°Ð½Ð¸Ðµ Ð½Ð°ÑÑ‹Ñ‰ÐµÐ½Ð¸Ñ Ñ‚ÐºÐ°Ð½Ð¸ Ð¿Ð»Ð°Ñ†ÐµÐ½Ñ‚Ñ‹ Ð³Ð»Ð¸Ñ†ÐµÑ€Ð¸Ð½Ð¾Ð¼ Ð¸ 1,2-Ð¿Ñ€Ð¾Ð¿Ð°Ð½Ð´Ð¸Ð¾Ð»Ð¾Ð¼ - Bobrova, E. N.; Zinchenko, A. V.; Schetinsky, M. I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2005)
Using differential scanning calorimetry and nuclear magnetic resonance methods we investigated placenta samples’ saturation with glycerol and 1,2-propane diol (1,2-PD). Placenta samples were exposed in 10, 40, 60% (w/w) glycerol and 1,2-PD solutions for 20, 60 min and 24 hrs. It was shown that in placenta tissue there was the formation of 1,2-PD solutions of higher concentrations for all saturating solutions with 1,2-PD in comparison with those with glycerol. A big amount of vitreous phase is formed in placenta for the same equilibration time in 1,2-PD-contained medium.